(untitled) (Paliativní medicína, 2022)
Shortness of breath is one of the basic symptoms of heart failure. Renin-angiotensin blockers, beta-blockers, mineralocorticoid receptor antagonists and sodium-glucose cotransporter 2 inhibitors currently form the basis for the treatment of dyspnoea in heart failure with reduced ejection fraction. Empagliflozin is newly used in the treatment of heart failure with preserved ejection fraction. Symptomatic treatment is based mainly on diuretics, parenteral iron substitution, in specific cases digoxin or inotropics are used. Opioids are used in the treatment of refractory dyspnea. Instrumental treatment also plays an important role, in the first place cardiac resynchronization, and mechanical cardiac support in indicated patients. Oxygen therapy is indicated in patients with hypoxemia. The use of individual procedures in a particular patient changes with the development of the disease and the change in the goals of care.